Mass. Gen. Stat. 107, ch. 13, § 113 (1859) - (:unkn) unknown (My University, 1859)
§A soldier who unnecessarily, or without order from a superior officer, comes to any parade, with his musket, rifle, or pistol, loaded with ball, slug, or shot, or so loads the same while on parade, or unnecessarily, or without order from a superior officer, discharges the same when going to, returning from, or upon parade, shall forfeit not less than five nor more than twenty dollars, to be recovered on complaint of the clerk, one-half to his use and one-half to the use of commanding officer.
Keywords: ARMED FORCES